2019
DOI: 10.12693/aphyspola.136.127
|View full text |Cite
|
Sign up to set email alerts
|

The Elastic, Electronic and Thermodynamic Properties of a New Cd Based Full Heusler Compounds - A Theoretical Investigation Using DFT Based FP-LMTO Approach

Abstract: In this paper, we present the first principle calculation of the different properties of the full Heusler compounds Cd2LaB, Cd2PrB, and Cd2CeB. Our calculations are based on density functional theory, using the full potential muffin-tin linear orbital method implemented in the LmtART code. For the determination of the exchange and correlation potential, we used the local density approximation and local spin density approximation. The elastic constants are also calculated. The total magnetic moment of Cd2LaB, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 17 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…In this work, we have made a prediction of structural, mechanical, electronic and optical properties using the FP‐LMTO method based on density functional theory (DFT) [23] with the calculation code LmtART 7.0 [24]. This method has has proven recently, to be one of the most accurate method for the calculation of the electronic structure of solids [25–27]. We have used the generalized gradient approximation (GGA) [28] to describe the energy of exchange and correlation by considering the effect of polarized spin, and the effective Hubbard parameter U eff = U − J , where U is the Coulomb interaction and J is the exchange parameter.…”
Section: Calculation Methodologymentioning
confidence: 99%
“…In this work, we have made a prediction of structural, mechanical, electronic and optical properties using the FP‐LMTO method based on density functional theory (DFT) [23] with the calculation code LmtART 7.0 [24]. This method has has proven recently, to be one of the most accurate method for the calculation of the electronic structure of solids [25–27]. We have used the generalized gradient approximation (GGA) [28] to describe the energy of exchange and correlation by considering the effect of polarized spin, and the effective Hubbard parameter U eff = U − J , where U is the Coulomb interaction and J is the exchange parameter.…”
Section: Calculation Methodologymentioning
confidence: 99%
“…Over the past few decades, semiconductor materials have attracted substantial attention due to their remarkable physical properties, making them adaptable to many modern technological applications. Of this large family, group III nitrides, particularly AlN, are characterized by a high melting point, high thermal conductivity, good dielectric strength, high degree of hardness, and direct wide band gap. These characteristics make AlN a suitable material for microelectronic substrate applications, short-wavelength light-emitting diodes, laser diodes, and optical detectors, as well as for high-temperature, high-power, and high-frequency devices. Consequently, extensive research has been conducted to characterize, as precisely as possible, the essential optical and electronic properties of AlN, which are of primary importance, as well as its mechanical and structural response. In contrast to the zincblende (ZB), wurtzite (WZ), and rock salt (RS) phases, no comprehensive experimental or theoretical investigation has been conducted on the polytypism of AlN.…”
Section: Introductionmentioning
confidence: 99%
“…These advantages make them the most promising spintronic device candidates. 6,7 Today, Heusler compounds are applied in a variety of disciplines of research, including spintronics, thermoelectrics, and superconductors. 8 So, thermoelectric coupling and spintronic devices are only two examples of where Heusler alloys find application in a wide variety of technological fields.…”
Section: Introductionmentioning
confidence: 99%
“…21 According to the findings, the Slater-Pauling rule applies to all investigated compounds, regardless of their magnetic or electronic properties, and as a result, all magnetic compounds are expected to have high Curie temperatures. Many studies 6,19 have shown the advantages of quaternary compounds. Because of its wide halfmetallic band gap and high deformation half-metallicity, it was revealed that CoCrIrSi is mechanically stable.…”
Section: Introductionmentioning
confidence: 99%